An International Spent Nuclear Fuel Storage Facility: Exploring a Russian Site as a Prototype: Proceedings of an International Workshop - National Research Council (The National Academies Press, 2005)
As part of a long-standing collaboration on nuclear nonproliferation, the National Academy of Sciences and the Russian Academy of Sciences held a joint workshop in Moscow in 2003 on the scientific aspects of an international radioactive disposal site in Russia. The passage of Russian laws permitting the importation and storage of high-level radioactive material (primarily spent nuclear fuel from reactors) has engendered interest from a number of foreign governments, including the U.S., in exploring the possibility of transferring material to Russia on a temporary or permanent basis. The workshop focused on the environmental aspects of the general location and characteristics of a possible storage site, transportation to and within the site, containers for transportation and storage, inventory and accountability, audits and inspections, and handling technologies.
Keywords: Environment and Environmental Studies

High-Energy Astrophysics: American and Soviet Perspectives/Proceedings from the U.S.-U.S.S.R. Workshop on High-Energy Astrophysics - National Academy of Sciences (The National Academies Press, 1991)
During the past decade, the field of astrophysics has progressed at an impressive rate. This was reflected by the topics discussed at the workshop from which this book eminated. These topics include the inflationary universe; the large-scale structure of the universe; the diffuse X-ray background; gravitational lenses, quasars and active galactic nuclei; infrared galaxies; results from infrared astronomical satellites; supernova 1987A; millisecond radio pulsars; quasi-periodic oscillations in the X-ray flux of low-mass X-ray binaries; and gamma-ray bursts.
Keywords: Space and Aeronautics

Nuclear Proliferation and Arms Control Monitoring, Detection, and Verification: A National Security Priority: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
At the request of Congress, this report presents findings and recommendations related to governance of the U.S. government's monitoring, detection, and verification (MDV) enterprise and offers findings and recommendations related to technical MDV capabilities and research, development, test, and evaluation efforts, focused in particular on the nuclear fuel cycle, nuclear test explosions, and arms control.
Keywords: Conflict and Security Issues

Setting the Stage for International Spent Nuclear Fuel Storage Facilities: International Workshop Proceedings - National Research Council (The National Academies Press, 2008)
In May 2003, the Russian Academy of Sciences and the National Academies organized an international workshop in Moscow on the scientific issues relevant to the establishment and operation of an international spent nuclear fuel storage facility in Russia. Given the broad international interest in this topic, the academies organized a second international workshop on important issues that were not on the agenda or were not adequately discussed at the first workshop. These issues included international monitoring at the facility, transportation requirements, liability and insurance concerns, and status of Russian legislation and regulations that are important in locating and operating a facility. Relevant experience from Europe, the United States, and Asia was also considered in this 2005 workshop. This book contains the papers presented at the 2005 workshop sessions, as well as proceedings from the 2003 workshop. Together they provide an overview of the issues, and useful background for those organizations and individuals involved in further development of an international spent nuclear fuel storage facility in Russia.
Keywords: Environment and Environmental Studies

Management and Disposition of Excess Weapons Plutonium: Reactor-Related Options - National Academy of Sciences (The National Academies Press, 1995)
Within the next decade, many thousands of U.S. and Russian nuclear weapons are slated to be retired as a result of nuclear arms reduction treaties and unilateral pledges. Hundreds of tons of plutonium and highly enriched uranium will no longer be needed for weapons purposes and will pose urgent challenges to international security. This is the supporting volume to a study by the Committee on International Security and Arms Control which dealt with all phases of the management and disposition of these materials. This technical study concentrates on the option for the disposition of plutonium, looking in detail at the different types of reactors in which weapons plutonium could be burned and at the vitrification of plutonium, and comparing them using economic, security and environmental criteria.
Keywords: Environment and Environmental Studies

The Comprehensive Nuclear Test Ban Treaty: Technical Issues for the United States - National Research Council (The National Academies Press, 2012)
This report reviews and updates the 2002 National Research Council report, Technical Issues Related to the Comprehensive Nuclear Test Ban Treaty (CTBT). This report also assesses various topics, including: the plans to maintain the safety and reliability of the U.S. nuclear stockpile without nuclear-explosion testing; the U.S. capability to detect, locate, and identify nuclear explosions; commitments necessary to sustain the stockpile and the U.S. and international monitoring systems; and potential technical advances countries could achieve through evasive testing and unconstrained testing. Sustaining these technical capabilities will require action by the National Nuclear Security Administration, with the support of others, on a strong scientific and engineering base maintained through a continuing dynamic of experiments linked with analysis, a vigorous surveillance program, adequate ratio of performance margins to uncertainties. This report also emphasizes the use of modernized production facilities and a competent and capable workforce with a broad base of nuclear security expertise.
Keywords: Conflict and Security Issues

Foreign and Foreign-Born Engineers in the United States: Infusing Talent, Raising Issues - National Research Council (The National Academies Press, 1988)
Keywords: Education

On Time to the Doctorate: A Study of the Lengthening Time to Completion for Doctorates in Science and Engineering - National Research Council (The National Academies Press, 1990)
A need exists for better models of what contributes to changes in the time that students take to complete doctorate degrees. Utilizing numerous data sources, On Time to the Doctorate presents a new model to explain changes in both total time to the doctorate and in the several components of time to the doctorate. It examines the lengthening time to the doctorate in many fields (chemistry; physics and astronomy; earth, atmospheric, and marine sciences; mathematical sciences; engineering; agricultural sciences; biological sciences; health sciences; psychology; economics; and "all other social sciences") and provides theoretical explanations for this lengthening time. This thorough and current analysis of time to the doctorate provides an up-to-date, extensive review of the literature and an exposition of data not available elsewhere.
Keywords: Education

Food Aid Projections for the Decade of the 1990s - National Research Council (The National Academies Press, 1988)
This book presents the results of a meeting held by the Board on Science and Technology for International Development. At this meeting, six groups of modelers presented their best estimates of the food aid/food commodity trade picture during the period 1991-2000. These estimates are based on each modeler's own database and own assumptions about trends in global policy, climate, population, and economics.
Keywords: Food and Nutrition

Microlivestock: Little-Known Small Animals with a Promising Economic Future - National Research Council (The National Academies Press, 1991)
Microlivestock is a term coined for species that are inherently small as well as for breeds of cattle, sheep, goats, and pigs that are less than about half the size of the most common breeds. These miniature animals are seldom considered in the broad picture of livestock development, but they seem to have a promising future, especially in developing nations or wherever land is scarce. This book raises awareness of the potential of these small species, including microcattle, microsheep, various poultry, rabbits, rodents, deer, antelope, and lizards. It also strives to stimulate their introduction into animal research and economic development programs.
Keywords: Agriculture

Strengthening Long-Term Nuclear Security: Protecting Weapon-Usable Material in Russia - National Research Council (The National Academies Press, 2006)
In July 2005, the National Academies released the report Strengthening Long-term Nuclear Security: Protecting Weapon-Usable Material in Russia. The report highlighted several obstacles in the transition from a U.S.-Russian cooperative program to a Russian-directed and Russian-funded fully indigenized program that will ensure the security of 600 tons of weapon-usable nuclear material at a level of international acceptability. Overcoming these obstacles requires an increased political commitment at a number of levels of the Russian Government to modern material protection, control, and accounting systems (MPC&A). Adequate resources must be provided to facilities where weapon-usable material is located for upgrading and maintaining MPC&A systems. Additionally, the technical security systems that are being installed through the cooperative program need to be fully embraced by Russian managers and specialists. The report recommends the establishment of a ten-year indigenization fund of about $500 million provided by Russia and its G-8 partners as a new mechanism for gradually shifting the financial burden of MPC&A to the Russian Government.
Keywords: Conflict and Security Issues

Approaches to Robotics in the United States and Japan: Report of a Bilateral Exchange (The National Academies Press, 1990)
Keywords: Engineering and Technology

The Flexible Electronics Opportunity - National Research Council (The National Academies Press, 2014)
Flexible electronics describes circuits that can bend and stretch, enabling significant versatility in applications and the prospect of low-cost manufacturing processes. They represent an important technological advance, in terms of their performance characteristics and potential range of applications, ranging from medical care, packaging, lighting and signage, consumer electronics and alternative energy (especially solar energy.) What these technologies have in common is a dependence on efficient manufacturing that currently requires improved technology, processes, tooling, and materials, as well as ongoing research. Seeking to capture the global market opportunity in flexible electronics, major U.S. competitors have initiated dedicated programs that are large in scope and supported with significant government funding to develop and acquire these new technologies, refine them, and ultimately manufacture them within their national borders. These national and regional investments are significantly larger than U.S. investment and more weighted toward later stage applied research and development. The Flexible Electronics Opportunity examines and compares selected innovation programs both foreign and domestic, and their potential to advance the production of flexible electronics technology in the United States. This report reviews the goals, concept, structure, operation, funding levels, and evaluation of foreign programs similar to major U.S. programs, e.g., innovation awards, S&T parks, and consortia. The report describes the transition of flexible electronics research into products and to makes recommendations to improve and to develop U.S. programs. Through an examination of the role of research consortia around the world to advance flexible electronics technology, the report makes recommendations for steps that the U.S. might consider to develop a robust industry in the United States. Significant U.S. expansion in the market for flexible electronics technologies is not likely to occur in the absence of mechanisms to address investment risks, the sharing of intellectual property, and the diverse technology requirements associated with developing and manufacturing flexible electronics technologies. The Flexible Electronics Opportunity makes recommendations for collaboration among industry, universities, and government to achieve the critical levels of investment and the acceleration of new technology development that are needed to catalyze a vibrant flexible electronics industry.
Keywords: Engineering and Technology

Cooperation in the Energy Futures of China and the United States--Chinese Version (The National Academies Press, 2000)
Keywords: Energy and Energy Conservation

Agricultural Water Management: Proceedings of a Workshop in Tunisia - National Research Council (The National Academies Press, 2007)
This report contains a collection of papers from a workshop—Strengthening Science-Based Decision-Making for Sustainable Management of Scarce Water Resources for Agricultural Production, held in Tunisia. Participants, including scientists, decision makers, representatives of non-profit organizations, and a farmer, came from the United States and several countries in North Africa and the Middle East. The papers examined constraints to agricultural production as it relates to water scarcity; focusing on 1) the state of the science regarding water management for agricultural purposes in the Middle East and North Africa 2) how science can be applied to better manage existing water supplies to optimize the domestic production of food and fiber. The cross-cutting themes of the workshop were the elements or principles of science-based decision making, the role of the scientific community in ensuring that science is an integral part of the decision making process, and ways to improve communications between scientists and decision makers.
Keywords: Earth Sciences

Technology Commercialization: Russian Challenges, American Lessons (The National Academies Press, 1998)
This collection of papers—by American and Russian specialists—addresses a variety of legal, regulatory, institutional, and financial issues that can promote or hinder technology commercialization. The book is the result of a series of workshops organized by the National Research Council with the Russian Academy of Sciences on commercialization of technologies, particularly those developed at research and educational institutions. Technology Commercialization concludes with a list of actions, programs, and policies which warrant further consideration as Russia tries to improve the success of technology commercialization. This book will be of interest to those concerned with small-business development in post-communist states, university technology management, and comparative technology commercialization.
Keywords: Industry and Labor; Biology and Life Sciences

Brain-Machine and Related Neural Interface Technologies: Scientific, Technical, Ethical, and Regulatory Issues: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Keywords: Engineering and Technology; Computers and Information Technology

Water Conservation, Reuse, and Recycling: Proceedings of an Iranian-American Workshop - National Research Council (The National Academies Press, 2005)
In December 2002, a group of specialists on water resources from the United States and Iran met in Tunis, Tunisia, for an interacademy workshop on water resources management, conservation, and recycling. This was the fourth interacademy workshop on a variety of topics held in 2002, the first year of such workshops. Tunis was selected as the location for the workshop because the Tunisian experience in addressing water conservation issues was of interest to the participants from both the United States and Iran. This report includes the agenda for the workshop, all of the papers that were presented, and the list of site visits.
Keywords: Earth Sciences; Environment and Environmental Studies

Assessment of the SBIR and STTR Programs at the National Institutes of Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Institutes of Health (NIH) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of its Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Using quantitative and qualitative analyses of data, this report reviews the operations and outcomes stemming from NIH's SBIR/STTR awards. Drawing on published research and conducting new analyses based on both publicly available data and applicant data provided by NIH, Assessment of the SBIR and STTR Programs at the National Institutes of Health analyzes (1) the effectiveness of NIH's processes and procedures for selecting SBIR and STTR awardees; (2) the effectiveness of NIH's outreach to increase SBIR and STTR applications from small businesses that are new to the programs, from underrepresented states, and from woman-owned and minority-owned businesses; (3) collaborations between small businesses and research institutions resulting from the programs; and (4) a range of direct economic and health care impacts attributable to the programs.
Keywords: Policy for Science and Technology

STTR: An Assessment of the Small Business Technology Transfer Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Today's knowledge economy is driven in large part by the nation's capacity to innovate. One of the defining features of the U.S. economy is a high level of entrepreneurial activity. Entrepreneurs in the United States see opportunities and are willing and able to assume risk to bring new welfare-enhancing, wealth-generating technologies to the market. Yet, although discoveries in areas such as genomics, bioinformatics, and nanotechnology present new opportunities, converting these discoveries into innovations for the market involves substantial challenges. The American capacity for innovation can be strengthened by addressing the challenges faced by entrepreneurs. Public-private partnerships are one means to help entrepreneurs bring new ideas to market. The Small Business Technology Transfer (STTR) and the Small Business Innovation Research (SBIR) program form one of the largest examples of U.S. public-private partnerships. In the SBIR Reauthorization Act of 2000, Congress tasked the National Research Council with undertaking a comprehensive study of how the SBIR program has stimulated technological innovation and used small businesses to meet federal research and development needs and with recommending further improvements to the program. When reauthorizing the SBIR and STTR programs in 2011, Congress expanded the study mandate to include a review of the STTR program. This report builds on the methodology and outcomes from the previous review of SBIR and assesses the STTR program.
Keywords: Industry and Labor